Variation of nickel accumulation in some broad-leaved plants by traffic density - Pulatoglu, Ayse Ozturk (Springer Science and Business Media LLC, 2025)
Urban areas with intense industrial activity and heavy traffic are among those most affected by increasing pollution levels. These areas experience a rise in air pollution, containing a complex mix of pollutants including particulate matter and potentially toxic elements. Trees located along urban and rural roadsides are used as environmentally sustainable tools for tracking and reducing air pollution impacts. In this study, the aim was to determine the variation of nickel (Ni) concentrations in the species Nerium oleander L., Salix babylonica L., Magnolia grandiflora L., Prunus laurocerasus L., Cercis siliquastrum L., Robinia pseudoacacia L., Aesculus hippocastanum L., Platanus orientalis L., and Acer negundo L. based on plant organs and traffic density. In this study, plant materials collected from the city center of Trabzon/Türkiye were used. The results indicate significant variations in Ni accumulation among species under different traffic densities based on average values. Differences in element concentrations have been observed both among the studied species and within the organs of the same species. Generally, the lowest Ni concentrations were observed in N. oleander (766.2 ppb), S. babylonica (935.7 ppb), and M. grandiflora (632.9 ppb), while the highest concentrations were recorded in R. pseudoacacia (3217.9 ppb) and A. negundo (3111.9 ppb). Therefore, R. pseudoacacia and A. negundo are considered suitable as bioindicator for Ni metal. These findings underscore the potential of plants to monitor heavy metal pollution from traffic and suggest that these species should be considered in environmental protection efforts.
Keywords: Air Pollutants; Turkey; Nickel; Air Pollution; Environmental Monitoring; Vehicle Emissions